Tourism Development Prospects in the Context of Global Socio-Economic Trends - PONKRATOVA, Liudmila Alexeevna; FEOKTISTOV, Sergei Vladimirovich; ADASHOVA, Tatiana Alekseevna; NIKOLSKAYA, Elena Yurievna; LIVSON, Maya Vladimirovna (Journal of Environmental Management and Tourism, 2021)
The article is devoted to assessing the tourism development prospects in the context of global socio-economic trends. It is revealed that the recreational nature of tourism directly affects the tourist attractiveness of Russian tourist territories since due to the vastness of the country it is exactly the regions where the necessary conditions for recreation and temporary stay in ecologically green areas can be created. It is proved that global socio-economic trends create prerequisites, that is, part of the conditions necessary to develop the tourism economy. These opportunities need to be actualized that may contribute to the emergence of conditions sufficient for turning the tourist potential of the regions into their real, financially tangible tourist attractiveness. The need to brand tourist destinations identifying unique features of the respective territories can be considered as the important steps towards tourism development.